SIMULASI SISTEM DINAMIK UNTUK MENINGKATKAN KINERJA RANTAI PASOK (Studi Kasus Di Industri Kulit PT Lembah Tidar Jaya Magelang) - Widodo, Eko Muh; Fatimah, Yun Arifatul; Indarto, Sigit (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
In an industry, information takes important role in every aspect involving industrial management. Inaccuracies will not only slowdown production process but also causes inefficiency in other processes. Research is conducted on supply chain performance indicators, namely product inventory level and order backlog. There are three major processes in PT Lembah Tidar Jaya Magelang, a company specializing in leather industry. These processes are Beam House Process, Retaining Process and Finishing Process. Indicator measurement for the three steps uses application of dynamic system simulation by using Based Model Order Information Sharing and Demand Sharing to understand the underlying structure that generates inventory fluctuations and order backlog size. Based on the evaluation of the system, the demand sharing model is proven to be more stable compared to the based model.